The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique